2017
DOI: 10.1007/s00216-016-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive polyphenol profiling of a strawberry extract (Fragaria × ananassa) by ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry

Abstract: The aim of metabolic untargeted profiling is to detect and identify unknown compounds in a biological matrix to achieve the most comprehensive metabolic coverage. In phytochemical mixtures, however, the complexity of the sample could present significant difficulties in compound identification. In this case, the optimization of both the chromatographic and the mass-spectrometric conditions is supposed to be crucial for the detection and identification of the largest number of compounds. In this work, a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…The polyphenol profile of strawberries shows that they have a highly diverse composition and La Barbera et al have confirmed or tentatively identified over 130 different individual compounds. The diversity of these compounds must be taken into consideration in fruit nutrition as their biological and pharmacological activities are specific to their chemical structure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyphenol profile of strawberries shows that they have a highly diverse composition and La Barbera et al have confirmed or tentatively identified over 130 different individual compounds. The diversity of these compounds must be taken into consideration in fruit nutrition as their biological and pharmacological activities are specific to their chemical structure .…”
Section: Introductionmentioning
confidence: 99%
“…A range of other phenolic compounds such as phenolic acids (hydroxycinnamic acids, p-coumaroyl, ferulic acid derivatives), stilbenes (resveratrol), and coumarins (p-coumaric acid), which are beneficial to human nutrition and health, have also been identified in strawberry fruits. 9,[11][12][13] However, the strawberry polyphenol profile can vary widely qualitatively and quantitatively as it is affected by various factors, including genotype, environmental factors, and their interactions. [14][15][16][17][18][19][20][21] The genetic makeup of strawberries is the most critical contributory factor in the variability of the nutritional quality of fruits in terms of total polyphenol content (TPC), total antioxidant content (TAC) and levels of individual polyphenols; however, growing conditions or environmental factors also play a significant role in determining the nutritional value of strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatographic method for systems (a) and (b) was chosen based on the work of La Barbera et al Phase B gradient was the following: 5–15% in 10 min, 15–35% in 15 min, 35–50% in 5 min, at 40°C (still air option), with ACN/HCOOH (99.9:0.1, v/v) as phase B and H 2 O/HCOOH (99.9:0.1, v/v) as phase A. The same conditions were kept for systems (c) and (d) but with the following gradient: phase B 5–15% in 20 min, 15–35% in 30 min, and 35–50% in 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The coelution of isomeric metabolites makes them indistinguishable and could generate ionization suppression of the less abundant compounds. Therefore, optimizing the chromatographic conditions in an untargeted analysis could be crucial for maximizing the number of detected and consequently identified compounds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation